Estudo do Mo na microestrutura e na resistência à corrosão em aço inoxidável duplex - Rezende, Stephania Capellari De (2018)
Due to the great technological evolution that has occurred in several areas of knowledge, increasingly requires the constant search for materials that have a set of features that meet the particular application, an example is the oil area that needs a material that support adverse conditions for exploration of oil. As a solution to this company emerged the duplex stainless steels, which have a combination of good mechanical properties and corrosion resistance, combining high strength and toughness with corrosion, stress corrosion cracking and weldability. As a way of product improvement aiming at the need for the industry, this project aims to make a comparison between duplex stainless steel SAF 2205 with the molybdenum element (Mo) (steel A) in its composition and the duplex stainless steel without Mo (steel B). The microstructural characterization of both steels revealed a typical microstructure of a duplex stainless steel composed of the austenite phase () in the form of elongated islands dispersed in the ferritic matrix (), with the presence of chi phase precipitates only in solubilized steel A for 240 min. X-ray diffraction revealed the presence of this characteristic peak of chi phase in steel A solubilized for 240 min, besides the characteristic peaks of the ferrite and austenite phases in steels A and B in all conditions studied. Quantitative stereology showed that the percentage ferrite phase increased significantly with increasing heat treatment time in both steels. The cyclic potentiodynamic polarization analyzes revealed that the best condition was the solubilization condition for 120 min in both steels. The result of the PREN of the ferrite and austenite phases of the B steel was less than 30, which would classify it as a Lean duplex, however this result was influenced by the absence of molybdenum alloy element, being a duplex stainless steel.